"Blown pack" Probabilistic Modeling for C. Algidicarnis and C. Estertheticum under the Effects of Storage Temperature, Vacuum Level and Package Shrink Temperature. (2016) - Silva, A.R.; Carvalho, J.; Massaguer, P.R.
Abstract: A model for 'blown pack' probability (BPP) caused by spores of C.estertheticum DSM8809 and C.algidicarnis, was developed as a function of vacuum packaging variables: storage temperature(ST:-2, 2, 4 and 15 °C), vacuum level(VL:6 and 9mBar) and heat shrink temperature(HST:83 and 87 °C). Beef meat pieces, were inoculated with spore suspensions individually at 10 2 spores/cm 2, packed and daily monitored up to 90 days. The lower BPP, estimated by the log-logistic model, for C.algidicarnis was 0.8% at:-1.5 °C/6mBar/87 °C while for C.estertheticum was 99.13% at the same conditions. For both organisms, tested variables were unable to eliminate the risk of blown packaged spoilage, at 10 2 spores/cm 2 contamination level.